Nurturing Inclusive Education through Cooperative Learning as Pedagogical Approach at Primary School Level - Muhammad Shahid Farooq, Iqra Asim (PJE, 2023)
Inclusive education is a way of reducing exclusion and increasing participation in such a way that responds effectively to the diverse needs of all learners without differentiating on the basis of their weaknesses and strengths. This approach with the use of cooperative learning strategies provides an ample opportunity to learners by developing a sense of community where their voices are heard and responded. This qualitative inquiry was planned to look at prospects of cooperative learning instructional strategies to foster inclusion in the learning environment.